EKSKLUSIVITAS SOSIAL : PENDEKATAN SISTEM PELAYANAN YANG TERINTEGRASI (INTEGRATED SERVICE DELIVERY SYSTEM APPROACH) - Niken L.V.A (Fakultas Ilmu Administrasi Universitas Brawijaya (FIA UB))
A major source of government failure in tackling social exclusion is the fragmentation and functional divisions within government. Exclusion is a dynamic and multidimensional process. It process driven by unequal power relationship in four main dimensions; economic, political, social and cultural – and at different levels including individual, household, group, community, country, and global levels. Generally, success of some managerial approaches to social exclusion, especially in dealing with “wicked Issues” of community safety, poverty, low income, poor health, need public institution reform. It could be taken place by having wider vision with three principal elements; community governance, co-production, co-evolution.Keywords: Social Exclusion, Integrating Public Service, Political Leadership